INTEGRATING AI CHATBOT INTO LEARNING MANAGEMENT SYSTEM: ENHANCING STUDENT ENGAGEMENT AND LEARNING OUTCOMES - Saifullah, Saifullah; Yawan, Hendri; Syafitri, Nining; Nurhaliza, Sitti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study investigates the integration of chatbots into Learning Management Systems (LMS) to enhance educational experiences, addressing the challenge of student engagement and support in digital learning environments. Utilizing a Research and Development (R&D) approach, the study systematically developed and implemented a chatbot within the